‘WHAT ARE YOU LOOKING FOR?’: SEXUAL IMAGINARIES AND AFFORDANCES ON GRINDR AND SCRUFF - Persaud, Christopher Jahmail; Liang, Calvin Alan (AoIR Selected Papers of Internet Research, 2023)
For queer men, sexual imaginaries have come to accomodate hybrid physical and digital location-based cultures (Miles, 2017). In short, what is possible in terms of intimate connections with other queer men has opened up in exciting, sometimes scary, and radical ways. However, this expanded imaginary of what is possible can also lead to an existential questioning of what an individual person wants—simply and nothing more than sex, a fleeting summer fling, a new group of friends, to fall in love? More? Less? A combination of all of these things at different moments in time? In the face of such uncertainty, we argue that queer men develop a range of practices as they negotiate their shifting relationships to sex and romance as mediated through virtual intimacies (McGlotten, 2013).In this study, we explore how queer men learn about, interpret, and reproduce sexual and romantic norms on two dating and hookup platforms, Grindr and Scruff. Our approach builds on Sharif Mowlabowcus’s (2016, pg. 60) notion of cybercarnality concerning the “erotic economy of gay male corporeality” and Pym et al. (2021, pg. 399) study of queer community “imagined as an affective sense of shared ethics” on intimate platforms. Drawing on our digital ethnographic and speculative design data, we develop the concept of _multivalent intimate interests_ to capture the ambivalent socio-cultural context and situated nature of queer men’s sexual and romantic practices.